The Effect of Tachiwaza on Motor Ability Improvement in Judo - Purnamasari, Ira; Febrianty, Mona Fiametta; Novian, Geraldi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
Giving basic judo moves in the form of Tachiwaza contributes to the overall development and coordination of the body. The provision of Tachiwaza material is intended so that the habit of exercising throughout life can be prepared early, so that children have fundamental basic movements that are useful for them throughout life. . Movement ability or also called motor ability is the ability to move in physical activity. This study aims to determine the effect of tachiwaza on increasing motor ability in Judo. This study used an experimental method using a sample of 12 children aged 6 to 12 years who took part in training in one of the training classes at the Judo club in Bandung. The sampling technique used is total sampling. The instrument used is a motor ability test, which consists of agility test with a 4x10 m shuttle run, a coordination test by throwing and catching a tennis ball with a distance of 1 meter from a wall, a balance test using a positional balance test, 4. Speed ​​test with the 30 meter sprint test. The result of this research is the data is normally distributed. From the data obtained and calculated using SPSS the results obtained are Tachiwaza training affects the increase in motor ability. This research can contribute that tachiwaza exercises can be used as an alternative exercise to improve children's motor abilities at the age of 6 to 12 years.